Organic Hydrogel Templates for Tunable Mesoporous Silica Hybrid Materials. Issue 1721 (2nd February 2015) - Kahn, Jennifer L.; Eren, Necla Mine; Campanella, Osvaldo; Voytik-Harbin, Sherry L.; Rickus, Jenna L.
ABSTRACT: Porous coatings at the surface of living cells have application in human cell transplantation by controlling the transport of biomolecules to and from the cells. Sol-gel-derived mesoporous silica materials are good candidates for such coatings, owing to their biocompatibility, facile solution-based synthesis conditions, and thin film formation. Diffusion and transport across the coating correlates to long-range microstructural properties, including pore size distribution, porosity, and pore morphology. Here, we investigated collagen-fibril matrices with known biocompatibility to serve as templating systems for directed silica deposition. Type 1 collagen oligomers derived from porcine skin are extensively characterized such that we can predict and customize the final collagen-fibril matrix with respect to fibril density, interfibril branching and viscoelasticity. We show that these matrices template and direct the deposition of mesoporous silica at the level of individual collagen fibrils. We varied the fibril density, silicic acid concentration, and time of exposure to silicifying solution and characterized the resulting hybrid materials by scanning electron microscopy, energy-dispersive x-ray spectroscopy, and rheology. Microstructural properties of the collagen-fibril template are preserved in the silica surface of hybrid materials. Results for three different collagen fibril densities, corresponding to shear storage moduli of 200 Pa, 1000 Pa, and 1600 Pa, indicate that increased fibril density increases the absolute amount of templated silica when all other silica synthesis conditions are kept constant. Additionally, mechanical properties of the hybrid material are dominated by the presence of the silica coating rather than the starting collagen matrix stiffness.